1972
DOI: 10.1071/bi9720619
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Glutathione Polymorphism in Sheep

Abstract: Reduced glutathione (GSH) levels of erythrocytes were determined in five sheep breeds. The Merino breed had a higher incidence of low GSH animals than the other breeds tested. High GSH type animals of the Border Leicester breed had a significantly lower mean GSH level than did higher GSH animals of the other breeds.GSH levels were found to be associated with electrolyte.levels, haemoglobin type, fleece weight, and body weight in Merino sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

1973
1973
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…Before we can decide whether or not Tf has any influence on GSH levels, we need to study a larger population since it may be due to the fact that this breed, in the present investigation, has the most variable Tf locus (Table 1) and is the smaller in numbers. The lack of significance for haemoglobin is in agreement with the data of AGAR et al (1972).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Before we can decide whether or not Tf has any influence on GSH levels, we need to study a larger population since it may be due to the fact that this breed, in the present investigation, has the most variable Tf locus (Table 1) and is the smaller in numbers. The lack of significance for haemoglobin is in agreement with the data of AGAR et al (1972).…”
Section: Discussionsupporting
confidence: 90%
“…In some earlier studies, GSH levels were studied in relation to genetic, physiological and environmental factors (AGAR et al 1972;ATROSHI 1979;ATROSHI et al 1980). Since in some breeds the question of number and kind of alleles and loci involved in the control of levels of this peptide is still unanswered as is the influence of environmental factors, we have undertaken to study the differences in three different ovine populations bred in Italy and to relate the GSH levels to some other factors.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that the haematocrit and haemoglobin concentration (Tucker and Ellory 1971; Agar et al 1972b), red cell life span (Agar et al 1975b), glycolysis (Agar and Smith 1973) and the concentration of glutathione precursors are similar in the red cells of normal and GSH-deficient sheep. Our results presented in Table 1 and Figs I and 2 provide further evidence that there are probably no differences in the biochemistry and/or physiology of the red blood cells of sheep with different levels of GSH.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic deficiency of aSH has been reported in the red blood cells of some sheep (Smith and Osburn 1967;Tucker and Kilgour 1970;Agar et al 1972b). This deficiency has been attributed to the lowered level (approximately 55% of normal) of activity of y-glutamyl-cysteine synthetase, one of the enzymes essential for de novo synthesis of glutathione from its precursor amino acids Young et al 1974).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation